2017
DOI: 10.1002/2017gl072874
|View full text |Cite
|
Sign up to set email alerts
|

A high‐accuracy map of global terrain elevations

Abstract: Spaceborne digital elevation models (DEMs) are a fundamental input for many geoscience studies, but they still include nonnegligible height errors. Here we introduce a high‐accuracy global DEM at 3″ resolution (~90 m at the equator) by eliminating major error components from existing DEMs. We separated absolute bias, stripe noise, speckle noise, and tree height bias using multiple satellite data sets and filtering techniques. After the error removal, land areas mapped with ±2 m or better vertical accuracy were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
715
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 1,030 publications
(829 citation statements)
references
References 45 publications
3
715
0
4
Order By: Relevance
“…Applying the RFS has two major advantages: first, it reduces run times as data exchange and computations need to be performed for a smaller number of cells; second, using RFS in large-scale applications with sufficient channel information reduces the dependency on the accuracy of remotely sensed 2-D elevation data such as Shuttle Rader Topographic Mission (SRTM) data (Farr et al, 2007). Recent research showed that such global data sets contain strong vertical bias as well as systematic and random noise (Yamazaki et al, 2017). In particular, simulating flow over vertically irregular terrain resulting in supercritical regimes is contraindicated for LFP because of its use of the LIE.…”
Section: The Computational Framework Glofrimmentioning
confidence: 99%
“…Applying the RFS has two major advantages: first, it reduces run times as data exchange and computations need to be performed for a smaller number of cells; second, using RFS in large-scale applications with sufficient channel information reduces the dependency on the accuracy of remotely sensed 2-D elevation data such as Shuttle Rader Topographic Mission (SRTM) data (Farr et al, 2007). Recent research showed that such global data sets contain strong vertical bias as well as systematic and random noise (Yamazaki et al, 2017). In particular, simulating flow over vertically irregular terrain resulting in supercritical regimes is contraindicated for LFP because of its use of the LIE.…”
Section: The Computational Framework Glofrimmentioning
confidence: 99%
“…This study used the MERIT DEM that Yamazaki et al (2017) produced by removing multiple error components from existing space-borne DEMs. The original MERIT DEM was developed with 3 arc second resolution by merging several baseline DEMs (Fig.…”
Section: Demmentioning
confidence: 99%
“…Iwahashi et al (2015) tried to create polygon data of terrain classification by object-based area segmentation (Baatz and Schäpe 2000) using the geometric signatures of Iwahashi and Pike (2007). In the current study, we develop this approach and introduce a trial of a new procedure of polygon-based classification using 280 m DEMs interpolated from the multi-error-removed improved-terrain DEM (MERIT DEM; Yamazaki et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the intertidal zone, we found abundant unevenness due to artificial water channels, and found that it was necessary to use elevation to determine the intertidal zone. 4 …”
Section: Resultsmentioning
confidence: 99%
“…Iwahashi et al [3] developed polygon data for global terrain classification using a combination of slope gradient, surface texture, and local convexity of the 280 m DEM interpolated from the Multi-Error-Removed Improved-Terrain (MERIT) DEM [4] . The results were generally suitable for distinguishing bedrock mountains, hills, large highland slopes, intermediate landforms (plateaus, terraces, and large lowland slopes), and plains.…”
Section: Introductionmentioning
confidence: 99%